Non-seizure SUDEP: Sudden Unexpected Death in Epilepsy without preceding epileptic seizures - Lhatoo, Samden D (Epilepsia, 2016)
OBJECTIVE: To describe the phenomenology of monitored Sudden Unexpected Death in Epilepsy (SUDEP) occurring in the inter-ictal period where death occurs without a seizure preceding it. METHODS: We report a case series of monitored definite and probable SUDEP where no electroclinical evidence of underlying seizures was found preceding death. RESULTS: Three patients (2 definite and 1 probable) suffered SUDEP. They had a typical high SUDEP-risk profile with longstanding intractable epilepsy and frequent generalized tonic-clonic seizures (GTCS). All patients had varying patterns of respiratory and bradyarrhythmic cardiac dysfunction with profound EEG suppression. In two patients, patterns of cardio-respiratory failure were similar to those seen in some patients in the Mortality in Epilepsy Monitoring Units Study (MORTEMUS). SIGNIFICANCE: Sudden Unexpected Deaths in Epilepsy (SUDEP) almost always occur postictally, after GTCS and less commonly after a partial seizure. Monitored SUDEP or near-SUDEP cases without a seizure have not yet been reported in literature. When non-monitored SUDEP occurs in an ambulatory setting without an overt seizure, the absence of EEG information prevents the exclusion of a subtle seizure. These cases confirm the existence of non-seizure SUDEP; such deaths may not be prevented by seizure detection based devices. SUDEP risk in epilepsy patients may constitute a spectrum of susceptibility wherein some are relatively immune, death occurs in others with frequent GTCS with one ultimately proving fatal, while in others still, death may occur even in the absence of a seizure. We emphasize the heterogeneity of SUDEP phenomena.